Pengaruh Lingkungan Kerja, Kepemimpinan dan Motivasi terhadap Employe Engagement pada Pegawai Dinas Koperasi Perdagangan dan Perindustrian Kabupaten Asahan - Nabilla Nabilla; Abdul Rahman (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Employee engagement is an important factor in improving employee performance and organizational effectiveness in the public sector. However, the achievement of several work programs at the Cooperatives, Trade, and Industry Office of Asahan Regency has not been optimal, indicating possible problems related to employee engagement. This study aims to analyze the effect of work environment, leadership, and work motivation on employee engagement among employees of the agency. The research used a quantitative approach with saturated sampling techniques involving 40 civil servants as respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis supported by validity, reliability, classical assumption, t-test, F-test, and coefficient of determination tests. The findings show that the work environment and work motivation have a positive and significant effect on employee engagement. Meanwhile, leadership does not significantly affect employee engagement partially. Simultaneously, the three independent variables significantly influence employee engagement. The coefficient of determination indicates that 54.3% of employee engagement can be explained by work environment, leadership, and work motivation, while the remaining 45.7% is influenced by other factors outside the study.